Obstacles Face Sixth-Semester English Students in Translating Proverbs from Arabic into English - Aleskandarani , Fouzia (Scientific Journal of University of Benghazi, 2024)
Translating proverbs is challenging, as they are culturally bound items. Thus, finding the most accurate equivalence causes problems for novice translators and learners. These problems are related to linguistic, cultural, and inaccurate use of translation techniques. Therefore, it is not reasonable to translate a proverb literally by just looking at the meaning of its individual words in a dictionary because they are culturally bound items. The current study attempts to investigate the problems that sixth-semester students encounter while translating Arabic proverbs into English and analyze the methods employed by them. The sample consists of 37 students in the English Department. The students were given a list of proverbs that contained 11 Arabic proverbs to be translated into English. The results revealed that students faced difficulties in translating proverbs due to cultural differences as well as overusing literal translation. The study recommended that students should use communicative translation, memorize some proverbs and their counterpart translations as well as practice.